A two-dimensional hybrid with molybdenum disulfide nanocrystals strongly coupled on nitrogen-enriched graphene via mild temperature pyrolysis for high performance lithium storage - Tang, Yanping; Wu, Dongqing; Mai, Yiyong; Pan, Hao; Cao, Jing; Yang, Chongqing; Zhang, Fan; Feng, Xinliang (Nanoscale, 2014)
A novel 2D hybrid with MoS2 nanocrystals strongly coupled on nitrogen-enriched graphene (MoS2/NGg-C3N4) is realized by mild temperature pyrolysis (550 °C) of a self-assembled precursor (MoS3/g-C3N4-H+/GO). With rich active sites, the boosted electronic conductivity and the coupled structure, MoS2/NGg-C3N4 achieves superior lithium storage performance. This journal is
CRIS-Team Scopus Importer:2023-03-20